2013
DOI: 10.1007/s11104-013-1593-4
|View full text |Cite
|
Sign up to set email alerts
|

Does geographic origin dictate ecological strategies in Acacia senegal (L.) Willd.? Evidence from carbon and nitrogen stable isotopes

Abstract: The NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 48 publications
3
28
2
Order By: Relevance
“…However, the ability to access deeper soil water and nutrients than crops contributes to improved nutrient cycling and increases the overall potential productivity of the system relative to monocropping with short-lived, shallow rooted crops. Stable isotope studies of Acacia senegal suggest plasticity in water use efficiency strategies, such that young shallow-rooted seedlings have high water use efficiency, but that this control is relaxed in older plants as their tap roots reach ground water (Gray et al, 2013).…”
Section: Tree Root Distribution and Root Activitymentioning
confidence: 99%
“…However, the ability to access deeper soil water and nutrients than crops contributes to improved nutrient cycling and increases the overall potential productivity of the system relative to monocropping with short-lived, shallow rooted crops. Stable isotope studies of Acacia senegal suggest plasticity in water use efficiency strategies, such that young shallow-rooted seedlings have high water use efficiency, but that this control is relaxed in older plants as their tap roots reach ground water (Gray et al, 2013).…”
Section: Tree Root Distribution and Root Activitymentioning
confidence: 99%
“…Authors also reported that the species when grown in areas with more precipitation does not produce gum even in the dry season. Recently, Gray et al (2013) reported that provenances of A. senegal that yielded more gum had low water use efficiency (WUE). This suggests that low WUE is actually associated to increased gum production.…”
Section: Genetic Improvement Of a Senegalmentioning
confidence: 99%
“…Afforestation plans to re-establish vegetation cover with N-fixing species such as Acacia species in degraded areas (Larwanou et al 2010) will depend on accurate knowledge of their growth and productivity and their performance in the environment selected. For example, results on seed, seedling and tree traits show that A. senegal from clay provenances can be quite distinct from those originating from sandy soil areas (Raddad et al 2005Raddad 2007;Gray et al 2013). Increasing the chances of producing and successfully establishing vigorous seedlings is a vital first step in improving re-vegetation .…”
Section: Introductionmentioning
confidence: 99%
“…Plant adaptation in arid climates generally involves great tolerance to drought, highly efficient utilization of water and nutrients, and greater biomass allocation to roots (Otieno et al 2005;Wu et al 2008;Gray et al 2013). Knowledge about shoot and root responses to water and nutrient stress may provide basic information for assessing differences among species in productivity, survival and distribution, and could shed more light on the functioning of dry-land ecosystems (Otieno et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation